Fenton-like catalyst and preparation method thereof

By combining polymer organic materials with activated carbon and metal oxides, Fenton-like catalysts are prepared, which solves the problems of easy loss of active components of the catalyst and unstable structurally, and achieves the stability and long-term effectiveness of the catalyst, simplifies the process flow and reduces costs.

CN119819312AActive Publication Date: 2025-04-15QINGDAO AGRI UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510139947.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-04-15
Estimated Expiration
2045-02-08

AI Technical Summary

Technical Problem

In the prior art, catalyst active ingredients are prone to loss, unstable structure, complex process, short inactivation cycle and difficult to regenerate.

Method used

Fenton-like catalysts are prepared by combining polymer organic materials with activated carbon and metal oxides with catalytic functions or salts thereof by high-temperature drying and calcining processes to form a stable composite structure to improve catalytic performance.

Benefits of technology

The stability and long-term effectiveness of the catalyst are achieved, the loss of active ingredients is reduced, the process flow is simplified, the cost is reduced, and the need for regeneration process is avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819312A_ABST
    Figure CN119819312A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sewage treatment, in particular to a Fenton-like catalyst and a preparation method thereof. According to the specific technical scheme, the preparation method comprises the following steps: dissolving a polymer organic material in an organic solvent, adding activated carbon powder, fully stirring, adding a metal oxide with a catalytic function or a salt thereof, curing with water, drying, and calcining to obtain the catalyst; the dosage of the macromolecular organic material is 10-30wt%, and the macromolecular organic material is at least one of cellulose acetate, cellulose acetate ester, polyethylene, polystyrene, polypropylene, polysulfone, polyether, polyamide, polycarbonate and acrylonitrile-styrene-butadiene copolymer. The problems of easy loss of active components, unstable structure, complex preparation process, short inactivation period, difficult regeneration and the like of the catalyst in the prior art are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sewage treatment, and in particular to a Fenton-like catalyst and a preparation method thereof. Background Art

[0002] High-concentration, difficult-to-degrade, and high-salt sewage mostly comes from the chemical, pharmaceutical and other industries. Due to its ultra-high COD, complex composition, and high salt inhibition of microorganisms, traditional biological methods are difficult to treat, and advanced oxidation technology has become the key. This technology uses active species such as strongly oxidizing hydroxyl radicals to oxidize and decompose pollutants, including Fenton, Fenton-like, photocatalytic, ozone and wet oxidation technologies. Among them, Fenton-like technology has outstanding advantages, with high efficiency, strong adaptability, simple operation and good cost-effectiveness, which is particularly valuable in high-salt sewage scenarios. The core of Fenton-like technology lies in catalysts, which are of various types. Common ones include iron-based zero-valent iron, iron oxides and loaded iron agents, as well as non-ferrous metals such as copper and manganese and multi-metal composite catalysts such as Fe-Mn. There are multiple preparation methods, such as the impregnation method, which is simple to operate and low in cost, but the loading capacity is limited; the co-precipitation method can evenly distribute metal ions but the precipitation conditions are difficult to control; the sol-gel method can be accurately constructed but the process is cumbersome; the hydrothermal method has high product activity but requires special equipment and harsh conditions.

[0003] In the process of sewage treatment, the leaching of metal ions is affected by many factors, including the chemical composition, crystal structure, surface properties of the material, and the environmental conditions such as temperature, pH value, solution composition, etc. For example, in some acidic or alkaline reaction systems, metal ions on the surface of metal oxide catalysts are more easily leached. Metal ion leaching may lead to reduced catalyst activity because the number of active centers is reduced. At the same time, the leached metal ions may cause side reactions in the reaction system, affecting the selectivity of the reaction and the distribution of products.

[0004] In the development process of the catalytic field, single-component and two-component metal catalysts play a key role and have different technical characteristics and applications. Single-component metal catalysts, represented by platinum, palladium, and nickel, have achieved remarkable results in basic reactions such as hydrogenation and dehydrogenation. Its catalysis is based on the bonding of the outer electron orbits of metal atoms with reactant molecules to induce activation and promote the reaction. However, with the increasing complexity of chemical synthesis, single-component catalysts have exposed many problems. In a complex reaction system, because there is only a single active center, the activity is difficult to improve, the selectivity is difficult to control, and the stability is poor. Faced with the delicate requirements of multi-step reactions, it is beyond their ability. Extreme conditions such as high temperature and high pressure will also damage the metal structure and reduce the catalytic performance.

[0005] Dual-component metal catalysts take advantage of the combination of two metals to produce significant synergistic effects. For example, the platinum-rhodium bimetallic catalyst used in automobile exhaust purification, platinum is responsible for the oxidation of carbon monoxide and hydrocarbons, and rhodium is responsible for the reduction of nitrogen oxides. The two work together to effectively promote the development of dual-component catalysts in responding to complex catalytic needs and expanding the scope of application, and promote the continuous advancement of catalytic technology.

[0006] The Chinese patent application with publication number CN110508286A discloses a method for preparing (Ni, Mg, Cu)Fe2O4 heterogeneous Fenton catalyst from nickel sulfide concentrate. The method realizes the effective utilization of mineral resources and is prepared through leaching, pretreatment, coprecipitation-calcination and other steps. The catalytic activity is high, and the photo-assisted heterogeneous Fenton reaction system composed of oxalic acid and visible light can efficiently degrade organic dyes. It is easy to recycle and reuse, has low preparation cost, and has good application prospects. However, the process conditions have high control requirements, the leaching step has limitations on the treatment of components in the raw materials, and currently only the application scenario of organic dye treatment under a specific photo-assisted heterogeneous Fenton reaction system is shown, and the scope of application needs to be expanded and verified.

[0007] The Chinese patent application with publication number CN115337952A discloses a one-step synthesis method of iron-manganese bimetallic oxide loaded with nitrogen vacancy carbon nitride. The method has the advantages of adopting a one-step synthesis method, simple and efficient steps, high catalytic efficiency of FeMnOx / g-C3N4-VN, complete removal of sulfamethoxazole within 50 minutes, and a reaction rate that is 6 times that of FeMnOx. The amount of metal ion dissolution is small, decreasing by 75% and 86% respectively. It also realizes the construction of a catalyst with high catalytic activity and low ion leaching, and has good application prospects in the field of persulfate advanced oxidation. The disadvantages are that the application range is narrow, the purity of raw materials and reaction conditions are stringent, and the application scenarios and condition control need to be expanded and improved. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a Fenton-like catalyst and a preparation method thereof, which solves the problems in the prior art of easy loss of active components of the catalyst, unstable structure, complex process, short deactivation cycle and difficulty in regeneration.

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] The invention discloses a preparation method of a Fenton-like catalyst. The method comprises the following steps: dissolving a high molecular organic material in an organic solvent, adding activated carbon powder, fully stirring, adding a metal oxide or a salt thereof having a catalytic function, curing with water, drying, and calcining to obtain the catalyst. The high molecular organic material is used in an amount of 10 to 30 wt %, and the high molecular organic material is at least one of cellulose acetate, cellulose acetate ester, polyethylene, polystyrene, polypropylene, polysulfone, polyether, polyamide, polycarbonate, and acrylonitrile-styrene-butadiene copolymer (ABS resin).

[0011] Preferably, the organic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, sulfolane, and acetonitrile.

[0012] Preferably, the mass ratio of the activated carbon to the high molecular organic material is 1:1 to 5:1, and the amount of the metal oxide or its salt having catalytic function is 1 to 20 wt%.

[0013] Preferably, the metal element in the metal oxide or its salt having catalytic function is at least one of iron, copper, cerium, platinum, palladium, ruthenium, nickel, cobalt, manganese, lanthanum and yttrium.

[0014] Preferably, the polymer organic material and the organic solvent are dissolved by stirring at a constant temperature of 10 to 80° C. for 8 to 12 hours; and then the mixture is allowed to stand for 8 to 12 hours to prepare a uniform solution.

[0015] Preferably, the drying temperature is 70-120° C. and the drying time is 2-6 hours.

[0016] Preferably, the calcination temperature is 100-800° C., and the calcination time is 10-60 min.

[0017] Correspondingly, a Fenton-like catalyst prepared by the above preparation method.

[0018] Correspondingly, a Fenton-like catalyst prepared by the above preparation method is used in treating sewage.

[0019] Preferably, the sewage contains o-toluenesulfonamide, and the concentration of o-toluenesulfonamide is 0.5-10 g / L.

[0020] The present invention has the following beneficial effects:

[0021] 1. The present invention has significant advantages in synthesizing composite activated carbon by using polymer organic materials as catalyst carriers. It can create a stable environment for active sites, prevent the loss of active ingredients to ensure stable catalytic performance, and ensure stable production efficiency and product quality. With its own strength and stability, it can cope with harsh conditions through precise process control, maintain structural integrity, ensure active site exposure and smooth catalytic reaction. In addition, because there is almost no deactivation, the regeneration process is eliminated. When the catalyst is depleted to a certain extent, the catalyst can be directly replenished, which can simplify the operation and maintenance links and improve production efficiency.

[0022] 2. The preparation process of the present invention has low dependence on complex parameters, the process is simplified, and the manpower and material costs are greatly reduced, which is conducive to large-scale industrial application; in terms of environmental protection, the preparation process is relatively clean.

[0023] 3. The shape and other properties of the catalyst can be customized as needed, and its function can be enhanced by adding metal oxides or their salts to meet various industrial needs; reduce the loss of catalysts, reduce costs, build an economic closed loop, reduce resource waste, and optimize the cost-effectiveness of the catalyst throughout its life cycle.

[0024] 4. The catalyst prepared by the present invention exhibits extraordinary characteristics in multiple key links. First, ions do not dissolve during use, which fundamentally eliminates the problem of catalyst deactivation caused by ion loss. Once put into use, there is no need for repeated regeneration operations, and the efficient catalytic state is maintained for a long time and stably, providing solid guarantee for industrial continuous production; second, the shape and pore size of the activated carbon can be precisely controlled, and it can be perfectly formed according to the predetermined requirements. At the same time, the pore structure can be meticulously regulated, and it can create an adaptive pore size distribution and porosity according to the strict standards for the size of adsorbed molecules in various industrial scenarios such as specific impurity adsorption in chemical production and harmful gas adsorption and purification in the environmental protection field, ensuring that the activated carbon can operate efficiently under different working conditions, and the catalytic site activity is high, and the overall catalytic performance is excellent; third, the catalyst is extremely convenient to use, completely eliminating the cumbersome regeneration process, and there is no need to repeatedly fill and remove the catalyst tank, which greatly reduces the manpower and time costs, and is more in line with the actual demands of large-scale engineering applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a SEM image of the CeFeCuOx / AC catalyst prepared in Example 1;

[0026] Figure 2 TEM image of the CeFeCuOx / AC catalyst prepared in Example 1;

[0027] Figure 3 Flow chart of treating wastewater using the CeFeCuOx / AC catalyst prepared in Example 1;

[0028] Figure 4is the removal efficiency at different OTSA concentrations;

[0029] Figure 5 The effect of different reaction systems on the degradation rate of OTSA;

[0030] Figure 6 The active species produced during microwave-induced catalytic oxidation by different quenchers;

[0031] Figure 7 The effect of the number of times the catalyst is used on the removal rate of OTSA and COD during the degradation of high-concentration OTSA;

[0032] Figure 8 The effect of the number of times the catalyst is used on the removal rate of OTSA and COD during the degradation of medium-concentration OTSA;

[0033] Fig. 9 This figure shows the effect of the number of times the catalyst is used on the removal rate of OTSA and COD during the degradation of low-concentration OTSA. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.

[0036] The invention discloses a preparation method of a Fenton-like catalyst. The specific process is as follows: adding a high molecular organic material into an organic solvent, stirring for 8 to 12 hours to dissolve at a constant temperature of 10 to 80 DEG C, and then standing the mixture for 8 to 12 hours to prepare a uniform solution; then adding activated carbon (AC) powder, stirring sufficiently, adding a metal oxide or a salt thereof with a catalytic function, curing with water (shaping can be performed during curing to prepare catalysts of different shapes), drying at 70 to 120 DEG C for 2 to 6 hours, and then calcining at 100 to 800 DEG C for 10 to 60 minutes to obtain the catalyst; the amount of the high molecular organic material is 10 to 30 wt%, the mass ratio of the activated carbon to the high molecular organic material is 1:1 to 5:1, the amount of the metal oxide or the salt thereof with a catalytic function is 1 to 20 wt%, and when the metal oxide or the salt thereof with a catalytic function adopts multiple metal oxides or the salt thereof, the amounts thereof are 1 to 20 wt% respectively.

[0037] The temperature of water curing is 10-90°C, and the pores of the catalyst can be regulated by controlling the temperature of water curing.

[0038] The polymer organic material is at least one of cellulose acetate, cellulose acetate ester, polyethylene, polystyrene, polypropylene, polysulfone, polyether, polyamide, polycarbonate and acrylonitrile-styrene-butadiene copolymer (ABS resin). The organic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, cyclopentane, and acetonitrile. The metal element in the metal oxide or its salt with catalytic function is at least one of iron, copper, cerium, platinum, palladium, ruthenium, nickel, cobalt, manganese, lanthanum and yttrium. Taking iron as an example: ferric oxide, ferric oxide, ferric chloride, ferrous chloride, ferric nitrate, ferric phosphate, etc.; taking copper as an example: copper oxide, copper chloride, copper nitrate, copper sulfate, etc.

[0039] A Fenton-like catalyst prepared by the above preparation method is used in treating wastewater containing o-toluenesulfonamide. The concentration of o-toluenesulfonamide is 0.5-10 g / L. In the process of degrading OTSA, microwave induction combined with an oxidant (H2O2) is used for degradation, the microwave power is 500-700 W, the time is 1.5-10 min, the amount of H2O2 added is 50-100 mL / L, and the concentration is 30%.

[0040] The present invention will be further described below in conjunction with specific embodiments.

[0041] Example 1

[0042] Preparation of Fenton-like catalysts:

[0043] (1) Prepare a solution with a total mass of 100 g. Each combination of polymer organic materials is weighed according to the polymer organic material accounting for 10 to 30 wt% of the mixed system. When dimethylformamide is selected as the organic solvent and combined with polysulfone, accurately weigh 20 g of polysulfone, then slowly add an appropriate amount of N,N-dimethylformamide, stir at 10 to 80°C for 8 to 12 hours using a magnetic stirrer to fully dissolve the polysulfone, and then let the mixture stand for 8 to 12 hours to prepare a uniform and stable solution with a mass fraction of 20%.

[0044] (2) After filtering through a 50-mesh sieve, carefully add activated carbon powder (with a mass ratio of 2:1 to the selected high molecular organic material) and continue stirring to allow it to completely blend with the solution.

[0045] (3) Adding various metal oxides with catalytic functions such as (Fe3O4), copper (CuO), and cerium (CeO2) in mass fractions of 1 to 20 wt% to the fully stirred mixture, and then pouring it into a square mold.

[0046] (4) The mold is cured by water with the water temperature controlled at 20°C. After it is cured and detached from the mold, the cured polymer mixture is immersed in deionized water. After 12 to 24 hours of soaking and curing, the organic solvent is completely transferred to the water. A paper cutter is used to cut the mixture into square particles with a side length of 5 mm.

[0047] (5) Dry in a beaker in a water bath at 60-80°C until there is no water stain on the surface, then place it in an oven at 70-120°C for drying for 2-6 hours, and then place it in a muffle furnace for calcination at 500°C for 20 minutes. The polysulfone undergoes moderate carbonization and structural rearrangement, and the metal oxide simultaneously completes the crystal transformation and the optimization and activation of the active sites, thereby obtaining a catalyst.

[0048] (6) Catalyst (CeFeCuO x / AC) was cooled and soaked in deionized water for 1-2 hours to remove the ash and interfering ions on the surface, and then transferred to a drying oven. The specific surface area of ​​the prepared catalyst was 80.601 m 2 / g, pore volume 0.075cm 3 / g, average pore size 3.740nm.

[0049] Prepared CeFeCuO x The scanning electron microscope (SEM) image of the / AC catalyst is shown in Figure 1 (The right view is a higher magnification) As shown, after loading the metal oxide, the surface of the catalyst presents smaller particles than the activated carbon support, which is due to the presence of a large number of metal oxide nanoparticles. Observed at a higher magnification, numerous active particles are dispersed on its surface. Although the support looks relatively uniform, there are also some aggregated particles, which confirms that the active ingredient has been successfully loaded.

[0050] Figure 2 CeFeCuO x Transmission electron microscopy (TEM) image of the AC / AC catalyst material. It can be seen that Fe, Cu and Ce are uniformly dispersed on the carbon skeleton. In addition, in CeFeCuO xIn the high-resolution transmission electron microscopy (HRTEM) image of / AC, lattice fringes of ferroferric oxide (Fe3O4) with (220) crystal plane (interplanar spacing d = 0.16nm), copper oxide (CuO) with (11-2) crystal plane (interplanar spacing d = 0.25nm), and cerium dioxide (CeO2) with (220) crystal plane (interplanar spacing d = 0.26nm) were observed. Lattice fringes of activated carbon (AC) with (002) crystal plane (interplanar spacing d = 0.15nm) were also observed. These results show that the prepared CeFeCuO x / AC has good crystallinity and is evenly distributed on the AC skeleton.

[0051] Example 2

[0052] With the continuous development of the pharmaceutical industry, sulfonamides, as an important class of drugs, have multiple functions, including antibacterial, anti-carbonic anhydrase and diuretic properties. Among them, o-toluenesulfonamide (OTSA) is an organic compound, which is not only a crucial precursor in drug preparation, but also widely used as a key raw material for synthetic artificial fibers, dyes and plastic additives. Therefore, the wastewater containing o-toluenesulfonamide generated in the chemical production process needs to be treated.

[0053] The process of catalyst treatment of wastewater is as follows Figure 3 shown.

[0054] 1. A microwave-induced catalytic degradation experiment of OTSA was carried out under a set microwave radiation power. The specific operation is as follows: 100 mL of OTSA solution (concentration of 10 g / L, initial pH value of 4.0), 60% (v / v) catalyst and 100 mL of 30% H2O2 were added to a 500 mL three-necked flask equipped with a condensation reflux device. After microwave radiation (700 W, 10 min), the supernatant of the solution was drawn with a syringe and filtered through a 0.45 μm water filter membrane to prepare a sample for testing.

[0055] 2. Effect of different OTSA concentrations

[0056] The removal efficiency at different OTSA concentrations can reflect the oxidation capacity of the system. Under the optimal operating parameters mentioned in Operation 1 above, Figure 4As shown in the figure, with the increase of OTSA concentration, the removal rate of OTSA and COD gradually decreases. This is because at lower OTSA concentrations, the number of free radicals exceeds the number of OTSA molecules, so the degradation efficiency is higher. On the contrary, when the initial OTSA concentration is high, more OTSA will be adsorbed on the pores and surface of the catalyst, occupying the active sites of H2O2, and ultimately reducing the OTSA degradation efficiency. For example, when the initial OTSA concentration is 2g / L, the removal efficiencies of OTSA and COD are 99.67% and 91.3%, respectively, which are 8.6% and 10.2% higher than those at 10g / L, respectively. Although high-concentration OTSA solutions can quickly capture free radicals to improve their utilization efficiency, the efficiency of free radical generation is reduced, resulting in a decrease in the overall degradation rate.

[0057] 3. Influence of different reaction systems

[0058] like Figure 5 As shown, MW, H2O2, AC and CeFeCuO x / AC have no significant effect on the degradation rate of OTSA. The degree of OTSA degradation is minimal only by thermal effect, catalytic adsorption and H2O2 oxidation, and the COD removal rates are only 5.7%, 10.1%, 13.3% and 15.1%, respectively. In the two-factor reaction system, microwaves induce hydrogen peroxide to produce a small amount of free radicals, which slightly increases the degradation rate. The interaction between MW and the original catalyst (AC) and the three-component catalyst generates high-temperature hot spots, which increases the degradation rate by 13.3% and 17.6%, respectively. When the catalyst is combined with hydrogen peroxide in the absence of MW radiation, the oxidation process is slow and the reaction time is short, resulting in a low COD removal rate. When microwaves, oxidants and catalysts work together, the best degradation effect is achieved, and the best result is achieved within 6 minutes. Compared with activated carbon, the degradation efficiency of CeFeCuOx / AC is significantly increased by 36.8%. This is because the original catalyst does not contain metal active components, which hinders the Fenton reaction in the system, resulting in a decrease in degradation efficiency. The MW-assisted Fenton-like reaction, combined with metal oxide-loaded catalysts and hydrogen peroxide, significantly shortened the reaction time and intensified the Fenton-like process.

[0059] Next, the microwave-enhanced Fenton-like catalytic oxidation mechanism was further explored. x / AC catalyst produces electron-hole pairs under microwave irradiation, which promotes the activation of H2O2 to produce free radicals. Metal ions participate in electron transfer to form a redox cycle to continuously activate H2O2. Organic matter is oxidized and mineralized after contact with free radicals, and finally produces water, carbon dioxide, nitrogen and sulfuric acid, achieving complete degradation of carbon and nitrogen. At the same time, it emphasizes the key role of electron transfer and each element in the reaction.

[0060] 4. Free Radical Capture Experiment

[0061] In the microwave (MW) induced catalytic oxidation system, hydroxyl radicals (·OH), electrons (e - ), hole (h + ) and superoxide anion radicals (·O2 - ) is considered to be the main active species for the removal of organic pollutants. The active species produced during microwave-induced catalytic oxidation were studied using p-benzoquinone (p-BQ), isopropyl alcohol (IPA), silver nitrate (AgNO3), potassium iodide (KI) and ascorbic acid (VC) as quenchers. Figure 6 As shown, the inhibitory effect is ranked as follows: OH>e - >h + >·O2 - OH was identified as the main free radical in the microwave-induced H2O2 catalytic oxidation process. After the introduction of p-benzoquinone, potassium iodide, silver nitrate and isopropanol, the COD removal rate dropped to 87.7%, 82.4%, 79.5% and 32.5%, respectively. This is because under MW irradiation, metal oxides are excited to generate electron-hole pairs (e - / h + ), water (H2O) and hydroxide ions (OH - ) and holes (h + ) reacts to generate OH and O2 - ·OH can be indirectly generated. In addition, MW induces the formation of active sites on the catalyst surface, which is conducive to the generation of ·OH by H2O2 at these sites. The addition of VC significantly inhibits the degradation efficiency of OTSA, indicating that it can effectively quench all free radicals. Therefore, ·OH plays a leading role in the degradation process, while e - 、h + and O2 - Play a secondary role.

[0062] Example 3

[0063] 1. Degradation of high concentration OTSA

[0064] The process conditions are as follows: OTSA concentration of 10g / L; MW power of 700W; time of 2min; H2O2 dosage of 100mL / L; pH value of 4; carbon column height of 50cm; initial temperature of 25℃. OTSA solution was introduced from the bottom of the reaction column. While keeping the microwave power and time constant, the microwave power and action time were adjusted. The OTSA concentration and COD removal rate of the effluent were measured, and the changes in degradation during repeated use were observed.

[0065] like Figure 7As shown in the figure, as the number of times of degradation increases, the OTSA and COD removal rates gradually decrease. By the fifth use, the two dropped to 68.7% and 71.2%, respectively, while the carbon loss rate increased from the initial 2.4% to 20.4%. This is because the activity of the catalyst may decrease after long-term use, which in turn causes changes in the reaction conditions and affects the degradation efficiency. As the number of uses increases, organic matter or other substances produced during the reaction may accumulate on the catalyst surface, forming a carbon deposition layer, which hinders the contact between the catalyst and the target substance in the wastewater, thereby reducing the reaction efficiency.

[0066] 2. Degradation of medium concentration OTSA

[0067] The process conditions are as follows: OTSA concentration of 1g / L; MW power of 500W; time of 1.5min; H2O2 dosage of 50mL / L; pH value of 4; carbon column height of 50cm; initial temperature of 25℃. OTSA solution was introduced from the bottom of the reaction column. While keeping the microwave power and time constant, the time, microwave power and action time were adjusted. The OTSA concentration and COD removal rate of the effluent were measured, and the changes in degradation during repeated use were observed.

[0068] like Figure 8 As shown in the figure, with the increase of degradation cycle number, the removal efficiency of OTSA and COD gradually decreased, and by the fifth cycle, they dropped to 83.7% and 71.5%, respectively. The carbon loss rate increased from the initial 1.6% to 12.4%.

[0069] 3. Degradation of low concentration OTSA

[0070] The process conditions are as follows: OTSA concentration of 50 mg / L; MW power of 500 W; time of 1.5 min; H2O2 dosage of 50 mL / L; pH value of 4; carbon column height of 50 cm; initial temperature of 25 ° C. OTSA solution was introduced from the bottom of the reaction column. While keeping the microwave power and time constant, the time, microwave power and action time were adjusted. The OTSA concentration and COD removal rate of the effluent were measured, and the changes in degradation during repeated use were observed.

[0071] like Fig. 9 As shown in the figure, with the increase of the number of uses, the removal rates of OTSA and COD gradually decreased. By the fifth use, the two dropped to 88.6% and 77.2%, respectively, while the carbon loss rate increased from the initial 0.8% to 9.5%. Under low concentration conditions, after five cycles, the removal rates of OTSA and COD decreased by 6% and 14.8%, respectively. This shows that CeFeCuOx / AC has excellent reusability.

[0072] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a Fenton-like catalyst, characterized in that: The high molecular organic material is dissolved in an organic solvent, activated carbon powder is added, and after sufficient stirring, a metal oxide or a salt thereof having a catalytic function is added, and after water solidification, the catalyst is obtained after drying and calcination; the amount of the high molecular organic material is 10 to 30 wt%, and the high molecular organic material is at least one of cellulose acetate, cellulose acetate ester, polyethylene, polystyrene, polypropylene, polysulfone, polyether, polyamide, polycarbonate and acrylonitrile-styrene-butadiene copolymer.

2. The preparation method according to claim 1, characterized in that: The organic solvent is at least one of N,N-dimethylacetamide, N,N-dimethylformamide, N-methylpyrrolidone, dimethyl sulfoxide, sulfolane and acetonitrile.

3. The preparation method according to claim 1, characterized in that: The mass ratio of the activated carbon to the high molecular organic material is 1:1 to 5:1, and the amount of the metal oxide or its salt having catalytic function is 1 to 20 wt%.

4. The preparation method according to claim 1 or 3, characterized in that: The metal element in the metal oxide or its salt having catalytic function is at least one of iron, copper, cerium, platinum, palladium, ruthenium, nickel, cobalt, manganese, lanthanum and yttrium.

5. The preparation method according to claim 1 or 2, characterized in that: The polymer organic material and the organic solvent are stirred for 8 to 12 hours at a constant temperature of 10 to 80° C. to dissolve; and the mixture is then allowed to stand for 8 to 12 hours to prepare a uniform solution.

6. The preparation method according to claim 5, characterized in that: The drying temperature is 70-120°C and the drying time is 2-6 hours.

7. The preparation method according to claim 6, characterized in that: The calcination temperature is 100-800°C, and the calcination time is 10-60 minutes.

8. A Fenton-like catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a Fenton-like catalyst prepared by the preparation method according to any one of claims 1 to 7 in treating sewage.

10. The use according to claim 9, characterized in that: The sewage contains o-toluenesulfonamide, and the concentration of the o-toluenesulfonamide is 0.5-10 g / L.

Citation Information

Patent Citations

  • Preparation of (Ni, Mg, Cu) Fe2O3 heterogeneous Fenton-like catalyst from nickel sulfide concentrate and use method thereof

    CN110508286A

  • Method for synthesizing iron-manganese bimetallic oxide loaded nitrogen vacancy-containing carbon nitride in one step

    CN115337952A

  • Activated carbon adsorption material, preparation method thereof and application of activated carbon adsorption material in field of catalytic decomposition of organic pollutants

    CN110732316A

  • Preparation of activated carbon supported catalyst applied to heterogeneous electro-Fenton degradation of organic wastewater

    CN111097415A

  • Preparation method and application of hollow prismatic ferrocobalt oxide heterogeneous Fenton-like catalyst

    CN115920899A